Indigenous languages in Canada (Canada Watch, 2020)
This booklet is an introduction to the linguistic study of the Indigenous languages spoken in Canada. The following topics are covered: approaching the study of Indigenous languages from an informed and respectful perspective; the geographical distribution of Indigenous languages in Canada; some notable structural properties of Indigenous languages; the writing systems used for Indigenous languages; the effects of contact between Indigenous and non-Indigenous languages; the current vitality of Indigenous languages in Canada.